Food‐related impulsivity in obesity and Binge Eating Disorder – a systematic review. Issue 6 (21st January 2013) - Schag, K.; Schönleber, J.; Teufel, M.; Zipfel, S.; Giel, K. E.
Summary Impulsivity towards food has been recognized as a potential factor leading to increased food intake in obesity. Patients suffering from binge eating disorder (BED) form a specific subgroup of obese people that might be characterized by increased impulsivity. These assumptions, although, have yet to be verified. Therefore, this review evaluates evidence for food‐related impulsivity in obese people with and without BED and examines possible differences between both populations. More precisely, evidence for the two components of impulsivity is analyzed separately: evidence for reward sensitivity, specifically, the urge for appetitive stimuli and evidence for rash‐spontaneous behaviour such as acting disinhibited with no regard for the consequences. Our search resulted in 51 articles demonstrating generally increased food‐related impulsivity. We found particular emphasis on increased reward sensitivity in obese people, which appeared to be more pronounced in people with BED. There was little and conflicting evidence, however, concerning increased rash‐spontaneous behaviour in obese people without BED, but consistent evidence of an increase in obese people with BED. All in all, the evidence supports the view that BED represents a specific phenotype of obesity with increased food‐related impulsivity. Taking these specific deficits into account can enhance the effectiveness of weight reduction programmes and psychotherapy.